JURIDICAL ANALYSIS OF ADMINISTRATIVE OFFENCES RELATED TO CORRUPTION - Гончарук, Степан Тихонович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: certain provisions of the current anti-corruption legislation of Ukraine have been investigated in the article; legal compositions of administrative offences related to corruption have been analyzed. Methods: logical-conceptual, comparative-statistic, cognitive-analytical, etc. Results: a concept of administrative offences related to corruption has been defined, attributes of their legal compositions have been considered. Some suggestions to improve the effectiveness of counteraction to corruption have been given. Discussion: the specifics of administrative liability for administrative offences related to corruption.